Structure and performance of the international agri-food trade: A comparative analysis in the new member states - Camelia Gavrilescu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
In the post-accession period, a common feature of the international agri-food trade of the new Member States was a significant increase in the volume and value of export and import flows, thus contributing to the increase in intra- and extra-Community trade. Despite these increases in total trade flows, only four of the 13 new Member States managed to record trade surpluses. This paper analyzes changes in the structure, volume, value and geographical orientation of international agri-food trade of these states, and trade performance is analyzed in terms of trade balance indicators (structure and value).
Keywords: F14; Q17; 330; agri-food trade; NMS (New Member States); trade balance